2019
DOI: 10.1002/2475-8876.12120
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance of buckling‐restrained brace outrigger system in various configurations

Abstract: The outrigger system is deemed an effective solution for mitigating the seismic responses of tall core‐tube‐type buildings. By incorporating a buckling‐restrained brace (BRB) in the outrigger system (BRB‐outrigger), the BRB‐outrigger reduces seismic response not only through the outrigger mechanism but also through the seismic energy dissipation from the BRB’s hysteretic response. This study investigates the seismic behavior of structures with a single layer BRB‐outrigger and proposes three types of BRB‐outrig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…As shown in Figure 10b1–b3,d1–d2, the modal damping ratios increase with the depth of the slit, while an optimal value exists for the total dissipater amount. According to the complex eigenvalue analysis results in the author's previous study, [ 9,21–23 ] the damped outrigger system was found to be the most effective in increasing only the first‐order mode damping ratio. Compared to this result, it is a noteworthy advantage of the damped braced tube system with the damping ratios of the second and third modes higher than 7%.…”
Section: Seismic Performance Of Damped Brace Tube System Incorporatin...mentioning
confidence: 99%
“…As shown in Figure 10b1–b3,d1–d2, the modal damping ratios increase with the depth of the slit, while an optimal value exists for the total dissipater amount. According to the complex eigenvalue analysis results in the author's previous study, [ 9,21–23 ] the damped outrigger system was found to be the most effective in increasing only the first‐order mode damping ratio. Compared to this result, it is a noteworthy advantage of the damped braced tube system with the damping ratios of the second and third modes higher than 7%.…”
Section: Seismic Performance Of Damped Brace Tube System Incorporatin...mentioning
confidence: 99%
“…The results indicate that the location of an outrigger is more significant than its rigidity. Lin and Takeuchi [20] investigated the seismic behavior of structures with a single layer bucklingrestrained brace-outrigger. They proposed three types of buckling-restrained brace-outrigger configurations for practical design purposes that fit different architectural requirements.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They investigated the seismic behavior of structures with a single layer BRB‐outrigger and proposed three types of BRB‐outrigger configurations for practical design purposes. [ 6 ] Du et al investigated the mix application of viscous dampers and BRBs by proposing a model with an additional damping ratio on the basis of developing a viscous damper priority placement analysis method. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%